A preliminary report on the use of Midodrine in treating refractory gastroesophageal disease: Randomized Double-Blind Controlled Trial: Midodrine and refractory gastroesophageal disease - Bagheri Lankarani, Kamran; Sivandzadeh, Gholam Reza; Zare, Marziyeh; Nejati, Mohammadali; Niknam, Ramin; Taghavi, Ali Reza; Ejtehadi, Fardad; Naini, Mahvash Alizade; Moini, Maryam; Anbardar, Mohammad Hossein; Peymani, Payam (Acta Biomedica Atenei Parmensis, 2020)
Background: Gastroesophageal reflux disease (GERD) is a common disease with various clinical presentations. Acid suppression with proton pump inhibitors and lifestyle modification may not lead to satisfactory response in a substantial portion of patients. We investigated the possible effect of midodrine in patients with refractory GERD. Methods: Patients suffering from GERD and were refractory to one-month course of pantoprazole 40mg twice daily entered the study. This was a pilot, randomized, double-blind, and placebo-controlled study. After randomization, one group received Midodrine 5mg before meals for one month, and the other group received placebo for the same period. Meanwhile, pantoprazole was continued 40mg twice daily in both arms. The severity of symptoms was evaluated by the visual scoring system. Quality of life (QoL) in both groups was measured using a standardized version of Quality of Life in Reflux and Dyspepsia questionnaire (QOLRAD). Results: A total of twenty patients were enrolled in this study. There was a significant interaction between the groups and time on all measured scores based on QOLRAD questionnaire. All the markers in the Midodrine group had significant improvement over time, but the placebo group did not show any significant improvement. Both visual severity score and total QoL score in Midodrine arm showed a U shape change during  6 weeks. Conclusions: Midodrine before a meal could be useful in alleviating symptoms and improving QoL in the patients with refractory gastroesophageal disease.